2021
DOI: 10.1007/s11033-021-06350-9
|View full text |Cite
|
Sign up to set email alerts
|

High-density mapping for gray leaf spot resistance using two related tropical maize recombinant inbred line populations

Abstract: The identi cation of QTL/genes to resist gray leaf spot (GLS) caused by Cercospora zeae-maydis or Cercospora Zeina plays an urgent role in improving GLS resistance in maize breeding practice. In our study, two groups of recombinant inbred line (RIL) populations derived from CML373×Ye107 (176 RILs) and were generated and subjected to genotyping-by-sequencing (GBS). GBS technology was used for large-scale single nucleotide polymorphism (SNP) discovery and simultaneous genotyping of all F 7 lines from two relate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 48 publications
(59 reference statements)
0
11
0
Order By: Relevance
“…Liu et al [ 9 ] identified seven QTLs associated with GLS resistance, with qRgls.yaas-8-1 , located within the bin 8.04 interval of chromosome 8, having the highest effect. Chen et al [ 20 ] genotyped two RIL populations, (CML373 × Ye107 and Chang7-2 × Ye107) and discovered 11 QTLs associated with GLS resistance, with individual QTLs explaining 2.05–24.00% of the phenotype variation. Qiu et al [ 21 ] used a near-isogenic line (NIL) population to localize QTL-qGLS8 for GLS resistance on chromosome 8.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [ 9 ] identified seven QTLs associated with GLS resistance, with qRgls.yaas-8-1 , located within the bin 8.04 interval of chromosome 8, having the highest effect. Chen et al [ 20 ] genotyped two RIL populations, (CML373 × Ye107 and Chang7-2 × Ye107) and discovered 11 QTLs associated with GLS resistance, with individual QTLs explaining 2.05–24.00% of the phenotype variation. Qiu et al [ 21 ] used a near-isogenic line (NIL) population to localize QTL-qGLS8 for GLS resistance on chromosome 8.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of resistance alleles into the genetic resources of breeding programs is made possible by marker-assisted selection (MAS) [ 102 , 106 ]. Improving GLS resistance in maize breeding techniques requires the rapid discovery of GLS-resistant quantitative loci (QTL)/genes [ 102 , 107 ].…”
Section: The Main Foliar Diseases Affecting Cerealsmentioning
confidence: 99%
“…Until the 1970s, it became prevalent in the eastern United States, resulting in serious economic losses (Donahue et al ., 1991; Coates & White, 1998). Up to now, GLS has spread throughout most of maize planting areas and has become one of the most important yield‐limiting maize diseases in the world (Ward et al ., 1999; Mueller et al ., 2016, 2020; Chen et al ., 2021). Although multiple Cercospora species have been isolated from maize leaves showing GLS lesions, only two of them ( C. zeae‐maydis and C. zeina ) are the causal agents of GLS (Wang et al ., 1998; Crous et al ., 2006).…”
Section: Introductionmentioning
confidence: 99%